Fiber reinforced concrete using empty fruit bunch (efb) waste - Nurnadianabila, Abd. Halim (2017)
Malaysia produced about half of the world palm oil production (10.8 million tonnes), thus making Malaysia as the world’s largest producer and exporter of palm oil during this period (Abdullah & Sulaiman, 2013). The empty fruit bunch (EFB) is produced after the fresh fruit bunch is processed to produce oil palm mill. Due to the abundance of empty fruit bunch waste that was produced, it also generates waste management problem. EFB waste can be processed into fiber and can be used for other purposes. In this study, the EFB fibers are used as an additive in the concrete to control cracking due to plastic and drying shrinkage (Vajje & Krishna, 2013). Other than that, the usage of natural fibers are able to increase the concrete strength and reduce the plastic and drying shrinkage that can induce structural cracks. The main objectives of this study are to identify the optimum percentage of empty fruit bunch (EFB) fiber and to study the mechanical properties of empty fruit bunch (EFB) fiber in the reinforced concrete. This paper presents the compressive strength test, flexural strength test and splitting tensile strength test to study the mechanical properties of the concrete. In this experimental study, grade 25 MPa of concrete is used with a mix proportion of 1:1.5:3. The EFB fiber with percentages 0.25%, 0.50%, 0.75% and 1.00% was added into the concrete mixtures. The result shows that, the optimum percentage of EFB fiber 0.25% was identified as the most suitable percentage to be added into the concrete mixture. The findings from this experimental study shows that the optimum percentage of EFB fiber able to increase the early strength up to 10% of the concrete compared to the normal concrete. On the other hand, the strength increased for the flexural strength result of EFB fiber concrete up to 10% compared to the control mix. However, the splitting tensile strength for the EFB fiber lower 6% compared to the control mix. But with the addition of 0.25% EFB fiber able to resist the crack compared to the control mix.